Viber is a Powerful Kick to Support Online Learning during the Covid Period at SDIT Permata Kota Probolinggo - Abdul Basit; Didit Yulian Kasdriyanto; Deka Matsusitha; Dewi Sindy Anggila; Widya Trisna Rahayuningdiah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the most effective ways to maximize online learning is to create learning media. One of the learning media that relies on technology-based applications is called Viber. Viber is an application to create interactive learning media to implement interesting and fun learning strategies. This requires the adaptation of information technology from all lines and types of education to provide up-to-date learning media based on contextual and dynamic learning. The development and use of computer technology in the education system can make reforms for a better and modern education system. Since the COVID-19 pandemic has forced the learning process to continue to maintain the stability of delivering material to students so that it is maintained. This activity was carried out at SDIT Permata Kota Probolinggo which is located on Jalan Tongkol No. 2 No. 6, Ex. Mayangan, Kec. Mayangan, Probolinggo City, East Java 67218. The aim is to improve the quality of learning through the use of interesting and interactive video scribe and animaker learning media.